Power Subunit: Sumber-sumber dan Implikasinya Bagi Organisasi - Wulani, Fenika (Kajian Manajemen dan Bisnis, 2010)
Power within an organization is something which subunits of the same level want to obtain. The sources of a subunit's power include its ability in coping with uncertainty, substitutability, centrality, and value congruence with top management. To acquire and use power, a subunit takes into account the organizational politics concept.